Role of renal denervation in the treatment of arterial hypertension: a review - A. Yu. Orekhov; L. K. Karazhanova (Российский кардиологический журнал)
Regardless of the fact that arterial hypertension is the focus of modern cardiology, resistance to therapy is still an important public health problem with adverse medical, social, and economic consequences. Aim of study: systematizing the available results of studies of the effectiveness of renal denervation in the treatment of patients with resistant AH. Search within databases (PubMed, Cochrane Library) was performed for randomized controlled studies of second-generation catheterassisted renal denervation and sham-controlled studies. We have used PRISMA protocol for preparing our paper. The neutral results of the SYMPLICITY HTN-3 study significantly weakened the interest of practical cardiology in this procedure, however recently published data from the EnligHTNed IDE, SPYRAL HTN OFF MED, and SPYRAL HTN-ON MED studies confirmed the effectiveness and safety of the technique. As the result the second-generation catheters (multielectrode catheters) used for renal denervation confirmed the effectiveness and safety of the procedure, and also expanded the technique usage beyond resistant hypertension. However, the question of the reliability of long-term effects of the procedure still remains, as well as establishing mechanisms to identify predictors of planned intervention responsiveness.